Increasing Self-Efficacy of Preservice Teachers in Early Field Experiences. Issue 7 (15th September 2022) - Anderson, Jared; Ressler, James D.; Wahl-Alexander, Zachary
Abstract: The primary goal of teacher education programs is to develop preservice teachers into quality future educators. Preparing these students of teaching for the realities of working with children in schools can be complex. Formal teacher training can offer detailed attention to the self-efficacy of candidates during coursework and early field experiences. The purpose of this article is to provide strategies to help teacher educators and supervisors of preservice teachers promote self-efficacy development. Strategies that are linked to improved practices in supervision, the use of feedback, and staging reflection are described. Additional examples of early field experiences are presented with detailed procedures for organizing learning activities.